Pyrazolyl two-dimensional Cu (I)-MOF crystal luminescent material as well as preparation method and application thereof

By using copper nitrate and pyrazole ligand containing 2.5 water, the single crystal growth problem in metal pyrazole coordination polymers was solved, and the material preparation of high quantum yield and broad excitation spectrum was achieved. It is suitable for a variety of optoelectronic devices and X-ray scanning imaging.

CN119751897AActive Publication Date: 2025-04-04WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411706723.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-04
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the field of metal pyrazole coordination polymers, the growth of single crystals remains a difficult problem, especially monovalent copper coordination polymers.

Method used

By using copper nitrate and pyrazole ligand containing 2.5 water as raw materials, a two-dimensional layered Cu(I)-MOF crystal luminescent material was prepared under mild conditions by a simple synthesis method.

Benefits of technology

The preparation of Cu(I)-MOF crystal luminescent materials with high quantum yield has high intensity, high stability and wide excitation spectrum. It is suitable for photoluminescent and electroluminescent devices and exhibits excellent performance in X-ray scanning imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751897A_ABST
    Figure CN119751897A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of crystal luminescent materials, and provides a pyrazolyl two-dimensional Cu (I)-MOF crystal luminescent material and a preparation method and application thereof.The preparation method of the pyrazolyl two-dimensional Cu (I)-MOF crystal luminescent material comprises the following steps that S1, cupric nitrate and pyrazole are placed in a reaction kettle, then an organic solvent and deionized water are added, and stirring is conducted till the cupric nitrate and the pyrazole are dissolved; and S2, heating the mixed solution in the step S1 to 100 DEG C, reacting for 18-24 hours, cooling, washing with an organic solvent, and drying to obtain the Cu (I)-MOF crystal luminescent material. The low-toxicity copper nitrate containing 2.5 water and the organic chromophore pyrazole ligand are used as raw materials, almost perfect 1: 1 coordination binding and two-dimensional layered stacking Cu (I)-MOF is synthesized, the preparation method is simple, the excellent luminescence characteristic is shown, and the quantum yield reaches 99.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystal luminescent materials, and in particular to a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material and a preparation method and application thereof. Background Art

[0002] With the rapid development of crystal engineering, the selection and design of ligands have attracted much attention. Ligands not only provide coordination ability, but also affect the entire network and topological structure by changing the coordination orientation. Pyrazole ligands have attracted much attention due to their versatility and stability. Pyrazole is a five-membered aromatic heterocycle containing two adjacent nitrogen atoms, which has two key characteristics: first, the hydrogen on the nitrogen atom can be easily removed to form anions, enhancing the affinity for metal ions; second, dehydropyrazole, as a 1,2-exo-bidentate ligand, has strong bridging ability. By adjusting the electronic and stereo characteristics of the substituents on the pyrazole ring, its coordination behavior can be regulated. This has caused extensive research interest in the field of organometallic chemistry for the complexes of pyrazole ligands and transition metals, especially low-coordination copper (I) complexes.

[0003] The structures of existing pyrazole-containing complexes may be roughly divided into the following types: (S1) Pyrazole is not dehydrogenated as a monodentate ligand, in which pyrazole is equivalent to a pyridine ligand; (S2) Pyrazole single-bridged complexes, which are a relatively mature type of pyrazole system research. According to the coordination configuration of the central metal atom, the position of the substituent on the pyrazole ring and the reaction conditions, various pyrazole complexes with different nuclei and configurations, homonuclear and heteronuclear, can be formed. Among this type of complexes, the most studied are pyrazole and +1 linear coordinated d 10 Polynuclear neutral complexes formed by metal (Cu) [Cu(pz)] n Such complexes usually form oligomers of pyrazole mononuclear and polynuclear copper clusters, or coordination polymers with pyrazole polynuclear copper clusters (binuclear, trinuclear, and hexanuclear structural units) as secondary building blocks.

[0004] Christopher J. Ziegler et al. used pyrazolyl ligands and two bromine atoms to form tetrahedral mononuclear oligomers with copper atoms; in [Cu(Htmpz)4(ClO4)2], the copper atom is hexacoordinated, coordinated with the nitrogen atoms of the four ligands and the oxygen atoms of the two perchlorate groups, forming a distorted octahedral structure. Pyrazole ligands connect two metal atoms to form binuclear structural units that are easy to form. Sometimes halogen atoms and carboxyl groups participate in bridging at the same time, often resulting in oligomers and one-dimensional chain structures. Bu Xianhe et al. used monopyridylpyrazole to react with copper salts to obtain binuclear units, which were stacked into one-dimensional chain polymers through hydrogen bonding. Pyrazole trinuclear metal unit complexes are the most common, easy to synthesize and have good performance. There are roughly several types of trinuclear unit structures: coplanar M3(Pz)3, non-coplanar M3(Pz)6, M3(Pz)3 bridged by halogen or acid ions, etc. This type of complex has a large number of oligomers and some coordination polymers connected to copper halogen clusters. For pyrazole complexes with higher nuclear numbers, the structures are mostly saddle-shaped, polyhedral, cage-shaped, and crown-shaped.

[0005] In summary, the growth of single crystals for metal pyrazole coordination polymers is still a difficult problem to solve, especially for monovalent copper coordination polymers. Compared with other single crystal synthesis methods (Angew.Chem.Int.Ed,2021,60,2534–2540.)(J.Am.Chem.Soc.1994,116,7668–7676.), the cubic Cu(I)-MOF crystals with two-dimensional layered structures synthesized in the present invention are relatively greener, simpler and less expensive, achieving perfect 1:1 coordination, and the two-dimensional Cu-MOF has a photon quantum yield of nearly 100%. With the help of a film-coating liquid, it also exhibits excellent performance as a device film material in X-ray scanning imaging. Summary of the invention

[0006] In view of this, the present invention proposes a preparation method and application of a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material with high quantum yield.

[0007] The technical solution of the present invention is implemented as follows: In the first aspect, the present invention provides a method for preparing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material, comprising the following steps:

[0008] S1, placing copper nitrate and pyrazole in a reaction kettle, then adding an organic solvent and deionized water, and stirring until dissolved;

[0009] S2, heating the mixed solution of step S1 to 100°C, reacting for 18-24 hours, cooling, washing with an organic solvent, and drying to obtain a Cu(I)-MOF crystal luminescent material.

[0010] On the basis of the above technical solution, preferably, the copper nitrate is Cu(NO3)2·2.5H2O, and the molar ratio of copper nitrate:pyrazole is 1.3-2:1.7-2.5.

[0011] On the basis of the above technical solution, preferably, during heating in step S2, the temperature is raised to 100° C. at a rate of 1 to 5° C. / min.

[0012] Based on the above technical solution, preferably, the organic solvents in steps S1 and S2 are N,N-dimethylformamide and anhydrous ethanol.

[0013] On the basis of the above technical solution, preferably, in step S1, the stirring time is 5 to 10 min, and the stirring rate is 300 to 800 rpm.

[0014] In a second aspect, the present invention provides a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material prepared by the above-mentioned preparation method.

[0015] In a third aspect, the present invention provides an application of a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material in the preparation of a Cu(I)-MOF@PMMA scintillator film material.

[0016] On the basis of the above technical solution, preferably, the preparation method of the MOF@PMMA scintillator film material comprises the following steps:

[0017] S1, dispersing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material and polymethyl methacrylate in a toluene solution to obtain a precursor turbid liquid, then dropping the precursor turbid liquid onto a glass substrate, and spin coating to form a precursor film;

[0018] S2, placing the precursor film in an oven for a first annealing, then peeling the annealed solidified film from the glass substrate, and performing a second annealing to obtain a MOF@PMMA scintillator film material.

[0019] On the basis of the above technical solution, preferably, the mass ratio of pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material: polymethyl methacrylate is 1-2:10-20.

[0020] On the basis of the above technical solution, preferably, the first annealing temperature is 40-60° C., and the time is 10 min; the second annealing temperature is 70-90° C., and the time is 5 min.

[0021] The pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material and its preparation method and application of the present invention have the following beneficial effects compared with the prior art:

[0022] (1) The present invention uses cheap, easily available, low-toxic copper nitrate containing 2.5 water and organic chromophore pyrazole ligand as raw materials to synthesize Cu(I)-MOF with nearly perfect 1:1 coordination and two-dimensional layered stacking. Its preparation process reduces the cost of crystal synthesis, the preparation method is simple, the product is easy to obtain, the synthesis process does not involve highly polluting, toxic chemical products or intermediates, is environmentally friendly, the reaction conditions are mild and controllable, and it can be prepared in large quantities for continuous production.

[0023] (2) The complex created by the present invention not only exhibits excellent luminescence properties, including high intensity, high stability and an amazing quantum yield of 99.8%, but also has the potential to significantly reduce energy loss in the application of large-area photoluminescent and electroluminescent devices. A major highlight of this material is its relatively broad excitation spectrum and narrow and symmetrical emission spectrum characteristics. This means that the complex can be effectively excited within a wide spectral range. As long as the energy of the excitation light exceeds a certain threshold, it can trigger its luminescence. Regardless of how the wavelength of the excitation light changes, its emission spectrum remains fixed and concentrated. This feature provides great flexibility and efficiency for the application of the complex in a variety of optoelectronic devices.

[0024] (3) The Cu(I)-MOF crystal luminescent material developed by the present invention forms a mixed matrix film with polymethyl methacrylate (PMMA) that can emit fluorescence pulses under X-ray irradiation. Therefore, the luminescent material is cleverly designed and used as a scintillator, closely combined with an electric conversion array and an advanced electronics system to form a high-performance X-ray detector. This innovative design enables the detector to achieve precise detection of X-rays under corresponding technical conditions. Therefore, it shows great application potential in X-ray scanning imaging technology and can provide strong technical support for many fields such as medical diagnosis, safety inspection, materials science and industrial testing. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a physical picture of the Cu(I)-MOF crystal luminescent material;

[0027] Figure 2 This is a physical picture of the Cu(I)-MOF@PMMA functional hybrid mixed matrix membrane;

[0028] Figure 3This is the SEM morphology test image of the Cu(I)-MOF crystal luminescent material of Example 1;

[0029] Figure 4 This is a SEM cross-sectional morphology test image of the Cu(I)-MOF crystal luminescent material of Example 1;

[0030] Figure 5 This is the XRD test pattern of the Cu(I)-MOF crystal luminescent material of Example 1;

[0031] Figure 6 This is a single crystal structure diagram of the Cu(I)-MOF crystal luminescent material of Example 1;

[0032] Figure 7 This is the TGA test graph of the Cu(I)-MOF crystal luminescent material of Example 1;

[0033] Figure 8 This is the solid ultraviolet absorption spectrum of the Cu(I)-MOF crystal luminescent material of Example 1;

[0034] Fig. 9 The photoluminescence spectrum of the Cu(I)-MOF crystal luminescent material of Example 1;

[0035] Fig.10 This is a graph showing the quantum yield of the Cu(I)-MOF crystal luminescent material prepared in Example 1;

[0036] Fig.11 , 12 13 are the actual photos and X-ray images of the MOF@PMMA scintillator film material prepared in Examples 4-6 before and after X-ray imaging; Figure 11-12 In the figure, A is the physical picture, B and C are X-ray images; Fig.13 In the figure, A and C are physical images, and B and D are X-ray images;

[0037] Fig.14 MOF@PMMA scintillator film photographed using a line pair card with standard X-ray resolution for Cu(I)-MOF crystal luminescent material. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The copper nitrate used in the present invention contains 2.5 crystal waters of copper (II) nitrate (Cu(NO3)2·2.5H2O), the purity of pyrazole is 99.98%, the resistivity of deionized water is 0.5MΩ*cm (25°C), and anhydrous ethanol is an analytical grade reagent.

[0040] Example 1

[0041] The preparation method of the pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material of this example comprises the following steps:

[0042] S1, 0.4 g Cu(NO3)2·2.5H2O and 0.136 g pyrazole (molar ratio 0.861:1, i.e. 1.464:1.7) were placed in the inner tank of a reactor;

[0043] S2, add 13.2 mL of N,N-dimethylformamide, 10 mL of deionized water and 13.2 mL of anhydrous ethanol to the reactor liner of step S1 in sequence, and stir at room temperature and 500 rpm for 8 min until completely dissolved to obtain solution A;

[0044] S3, completely sealing the reaction kettle containing solution A in step S2 and placing it in a forced air drying oven, heating it to 100°C at a rate of 2°C / min, keeping it at 100°C for 20 hours, and then cooling it naturally to obtain a two-dimensional Cu(I)-MOF crystal luminescent material;

[0045] S4, taking out the material obtained in step S3 using a rubber-tipped dropper and transferring it to a 100-mL beaker, pouring N,N-dimethylformamide into the beaker twice, 30 mL each time for washing to remove trace amounts of unreacted pyrazole and crystalline luminescent materials with poor crystallinity; then pouring anhydrous ethanol three times, 50 mL each time for washing, so as to further remove unreacted monomers and the N,N-dimethylformamide used for the above washing, so as to facilitate the drying and use of the material, and after drying, a two-dimensional Cu(I)-MOF crystalline luminescent material is obtained.

[0046] According to tests, the quantum yield of the two-dimensional Cu(I)-MOF crystal luminescent material prepared in this embodiment is 99.86%, which is close to 100%.

[0047] Example 2

[0048] The preparation method of the pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material of this example comprises the following steps:

[0049] S1 0.4 g Cu(NO3)2·2.5H2O and 0.2 g pyrazole (molar ratio 0.59:1, i.e. 1.3:2.2) were placed in the reactor liner;

[0050] S2. Add 13.2 mL of N,N-dimethylformamide, 10 mL of deionized water and 13.2 mL of anhydrous ethanol to the reactor liner of step S1 in sequence, and stir at room temperature at 800 rpm for 5 min until completely dissolved to obtain solution A.

[0051] S3: The reaction kettle containing solution A in step S2 is completely sealed and placed in a forced air drying oven, and the temperature is raised to 100°C at a rate of 1°C / min, and kept at 100°C for 18 hours, and then cooled naturally;

[0052] S4: The material obtained in step S3 is taken out using a rubber-tipped dropper and transferred to a 100-mL beaker. N,N-dimethylformamide is poured into the beaker twice, 30 mL each time, for washing to remove trace amounts of unreacted pyrazole and crystalline luminescent materials with poor crystallinity; then anhydrous ethanol is poured three times, 50 mL each time for washing, so as to further remove unreacted monomers and the N,N-dimethylformamide used for the above washing, so as to facilitate the drying and use of the material, and after drying, a two-dimensional Cu(I)-MOF crystalline luminescent material is obtained.

[0053] According to the test, the quantum yield of the two-dimensional Cu(I)-MOF crystal luminescent material prepared in this embodiment is 99.75%.

[0054] Example 3

[0055] The preparation method of the pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material of this example comprises the following steps:

[0056] S1 0.4 g Cu(NO3)2·2.5H2O and 0.146 g pyrazole (molar ratio 2:2.5) were placed in the reactor liner;

[0057] S2. Add 13.2 mL of N,N-dimethylformamide, 10 mL of deionized water and 13.2 mL of anhydrous ethanol to the reactor liner of step S1 in sequence, and stir at room temperature at 300 rpm for 10 min until completely dissolved to obtain solution A;

[0058] S3: The reaction kettle containing solution A in step S2 is completely sealed and placed in a forced air drying oven, and the temperature is raised to 100°C at a rate of 5°C / min, and kept at 100°C for 24 hours, and then cooled naturally;

[0059] S4: The material obtained in step S3 is taken out using a rubber-tipped dropper and transferred to a 100-mL beaker. N,N-dimethylformamide is poured into the beaker twice, 30 mL each time, for washing to remove trace amounts of unreacted pyrazole and crystalline luminescent materials with poor crystallinity; then anhydrous ethanol is poured three times, 50 mL each time for washing, so as to further remove unreacted monomers and the N,N-dimethylformamide used for the above washing, so as to facilitate the drying and use of the material, and after drying, a two-dimensional Cu(I)-MOF crystalline luminescent material is obtained.

[0060] According to the test, the quantum yield of the two-dimensional Cu(I)-MOF crystal luminescent material prepared in this embodiment is 99.81%.

[0061] Table 1 Crystallographic data of Cu(I)-MOF crystal luminescent material prepared in Example 1

[0062]

[0063]

[0064] Comparative Example 1

[0065] The difference between Comparative Example 1 and Example 1 is that the amounts of Cu(NO3)2·2.5H2O and pyrazole are different, namely: 0.465gCu(NO3)2·2.5H2O and 0.272gpyrazole (molar ratio 0.5:1), and the rest of the contents are the same as Example 1.

[0066] After drying, a flocculent material was obtained. The photon yield of the material obtained in Comparative Example 1 was tested to be 90%.

[0067] Comparative Example 2

[0068] The difference between Comparative Example 2 and Example 1 is that the amounts of Cu(NO3)2·2.5H2O and pyrazole are different, namely: 0.93g Cu(NO3)2·2.5H2O and 0.136g pyrazole (molar ratio 2:1), and the rest of the contents are the same as Example 1.

[0069] After drying, a flocculent material was obtained. The photon yield of the material obtained in Comparative Example 2 was tested to be 86%.

[0070] Comparative Example 3

[0071] The difference between Comparative Example 3 and Example 1 is that the amounts of Cu(NO3)2·2.5H2O and pyrazole are different, namely: 0.465g Cu(NO3)2·2.5H2O and 0.68g pyrazole (molar ratio 0.2:1), and the rest of the contents are the same as Example 1.

[0072] After drying, no crystalline luminescent material was obtained. After testing with an ultraviolet analyzer, the material obtained in Comparative Example 3 had very weak fluorescence characteristics under irradiation with ultraviolet lamps of 254 nm and 365 nm wavelengths.

[0073] Comparative Example 4

[0074] The difference between Comparative Example 4 and Example 1 is that the amounts of Cu(NO3)2·2.5H2O and pyrazole are different, namely: 2.326g Cu(NO3)2·2.5H2O and 0.136g pyrazole (molar ratio 5:1), and the rest of the contents are the same as Example 1.

[0075] After drying, no crystalline luminescent material was obtained. After testing with an ultraviolet analyzer, the material obtained in Comparative Example 4 had very weak fluorescence characteristics under irradiation with ultraviolet lamps at wavelengths of 254 nm and 365 nm.

[0076] Comparative Example 5

[0077] The difference between Comparative Example 5 and Example 1 is that the amounts of Cu(NO3)2·2.5H2O and pyrazole are different, namely: 0.465g Cu(NO3)2·2.5H2O and 1.36g pyrazole (molar ratio 0.1:1), and the rest of the contents are the same as Example 1.

[0078] After drying, a needle-shaped crystal luminescent material was obtained. The light quantum yield of the material obtained in Comparative Example 5 was tested to be 46%.

[0079] Comparative Example 6

[0080] The difference between Comparative Example 6 and Example 1 is that the amounts of Cu(NO3)2·2.5H2O and pyrazole are different, namely: 4.65g Cu(NO3)2·2.5H2O and 0.126g pyrazole (molar ratio 10:1), and the rest of the contents are the same as Example 1.

[0081] After drying, a needle-shaped crystal luminescent material was obtained. After testing, the light quantum yield of the material obtained in Comparative Example 6 was 52%.

[0082] Comparative Example 7

[0083] Comparative Example 7 provides a two-dimensional Zn-MOF crystal luminescent material and a preparation method thereof. The raw materials are 0.126 g pyrazole and 0.35 g zinc (II) nitrate, and the remaining steps are the same as Example 1.

[0084] After drying, no crystalline luminescent material was obtained. After testing with an ultraviolet analyzer, the material obtained in Comparative Example 7 had very weak fluorescence characteristics under irradiation with ultraviolet lamps at wavelengths of 254 nm and 365 nm.

[0085] Comparative Example 8

[0086] Comparative Example 8 provides a two-dimensional Co-MOF crystal luminescent material and a preparation method thereof. The raw materials are 0.126 g pyrazole and 0.34 g cobalt (II) nitrate, and the remaining steps are the same as Example 1.

[0087] After drying, no crystalline luminescent material was obtained. A simple test using an ultraviolet analyzer showed that the material obtained in Comparative Example 8 had no fluorescent properties under irradiation with ultraviolet lamps at wavelengths of 254 nm and 365 nm.

[0088] Comparative Example 9

[0089] Comparative Example 9 provides a two-dimensional Fe-MOF crystal luminescent material and a preparation method thereof. The raw materials are 0.126 g pyrazole and 0.34 g iron (II) nitrate, and the remaining steps are the same as Example 1.

[0090] After drying, no crystalline luminescent material was obtained. A simple test using an ultraviolet analyzer showed that the material obtained in Comparative Example 9 had no fluorescent properties under irradiation with ultraviolet lamps at wavelengths of 254 nm and 365 nm.

[0091] Comparative Example 10

[0092] Comparative Example 10 provides a two-dimensional Cu(I)-MOF crystal luminescent material and a preparation method thereof. The raw materials are 0.19 g tetrachloropyrazole and 0.4 g Cu(NO3)2·2.5H2O, and the remaining steps are the same as those in Example 1.

[0093] After drying, a crystalline luminescent material was obtained. After a simple test using an ultraviolet analyzer, the material obtained in Comparative Example 10 had no fluorescence properties under irradiation with ultraviolet lamps at wavelengths of 254 nm and 365 nm.

[0094] Comparative Example 11

[0095] Comparative Example 11 provides a two-dimensional Cu(I)-MOF crystal luminescent material and a preparation method thereof. The raw materials are 0.36 g of tetraiodopyrazole and 0.4 g of Cu(NO3)2·2.5H2O. The remaining steps are the same as those in Example 1.

[0096] After drying, a crystalline luminescent material was obtained. After a simple test using an ultraviolet analyzer, the material obtained in Comparative Example 11 had no fluorescent properties under irradiation with ultraviolet lamps at wavelengths of 254 nm and 365 nm.

[0097] After testing and comparing Examples 1-3, only Example 1 is a two-dimensional Cu-MOF crystal luminescent material with a 1:1 coordination structure, and its quantum yield is close to 100%.

[0098] It can be seen from the comparative examples 1-2 that when the molar ratio of pyrazole to copper (II) nitrate containing 2.5 crystal waters is 1:2 or 2:1, flocculent crystals are generated. When the ligands are slightly more, they can still fully coordinate with the reactants and promote the reaction. In this case, although the number of ligands is slightly more, it does not exceed the critical point, so it will not significantly inhibit the reaction, but continue to promote material generation. The kinetics of the reaction and the function of the ligand determine that the ligand changes within a certain range can be absorbed by the system and will not hinder the generation of the target product.

[0099] Comparative Examples 3-4 show that when the molar ratio of pyrazole to copper (II) nitrate containing 2.5 crystal waters is 1:5 or 5:1, no crystals are finally generated. Since the concentration of the ligand is too high, it will deviate from the ideal equilibrium state, making it difficult for the ligand to dissociate in the reaction system, thereby affecting the reaction and the formation of the product; more ligands will also form a larger steric barrier around the metal center, hindering other reactants from approaching the active center, thereby reducing the reaction rate and product yield.

[0100] Comparative Examples 5-6 show that when the molar ratio of pyrazole to copper (II) nitrate containing 2.5 crystal waters is 1:10 or 10:1, needle-shaped materials are generated. Adding ligands makes the side reactions more significant, thereby generating other materials different from the target product. It also changes the crystallization behavior in the system, resulting in the generation of more crystals or different crystal forms.

[0101] As can be seen from Comparative Example 7, the obtained material did not obtain crystals, but the obtained material had weak fluorescence characteristics. + When combined with pyrazole ligands to form complexes, Zn2 + Ions affect the electronic structure of pyrazole. This coordination may lead to rearrangement of the π electron system of the pyrazole ligand or change of energy level, making the transition between molecular orbitals more likely, especially the radiative transition from the excited state back to the ground state, thus producing fluorescence. + The coordination chemistry can significantly affect the electronic structure of the ligand. By forming a coordination bond with pyrazole to polarize the electron cloud of the ligand, the energy level structure of the ligand changes, thereby enhancing the fluorescence properties.

[0102] Comparative Examples 8-9 show that Co and Fe cannot synthesize corresponding crystalline luminescent materials with this method and the obtained materials have no fluorescence characteristics. Comparative Examples 10-11 show that although crystals are obtained using tetraiodine pyrazole and tetrachloropyrazole, there is no fluorescence characteristic under the irradiation of ultraviolet lamps with wavelengths of 254nm and 365nm. Tetraiodine pyrazole and tetrachloropyrazole contain heavy atoms (iodine and chlorine), which can enhance spin-orbit coupling, thereby increasing the possibility of intersystem crossing (non-radiative transition from singlet to triplet). This means that more excited state energy is released through non-radiative pathways (such as heat energy), rather than released by luminescence.

[0103] Figure 1 The Cu(I)-MOF crystal luminescent material prepared in Example 1 can be observed from the figure and has obvious fluorescence phenomenon under ultraviolet light.

[0104] Figure 2 The Cu(I)-MOF crystal and PMMA mixed matrix membrane material prepared in Example 1, as shown in the figure, the prepared membrane material has a regular three-dimensional cubic block shape, and the Cu(I)-MOF crystal luminescent material is evenly mixed in PMMA.

[0105] Figure 3 , 4 This is the SEM morphology test image of the Cu(I)-MOF crystal luminescent material prepared in Example 1. As can be seen from the SEM image of the prepared Cu(I)-MOF crystal luminescent material, the surface and cross-sectional morphology structure of the material are uniform and dense in layered stacking.

[0106] Figure 5 The XRD test pattern of the Cu(I)-MOF crystal luminescent material prepared in Example 1 was compared with the XRD spectrum simulated by the CIF file. The results showed that the test results were consistent with the fitting results.

[0107] Figure 6 This is a single crystal structure diagram of the Cu(I)-MOF crystal luminescent material prepared in Example 1. As can be seen from the figure, the material has a cubic crystal structure formed by 1:1 coordination of Cu(I) and pyrazole groups.

[0108] Figure 7 This is the TG test graph of the Cu(I)-MOF crystal luminescent material prepared in Example 1. According to the graph, the mass of the material remains basically unchanged at temperatures below 300°C, and decreases by about 40% at 600°C, indicating that the material has excellent thermal stability.

[0109] Figure 8 This is the solid ultraviolet absorption spectrum of the Cu(I)-MOF crystal luminescent material prepared in Example 1. According to the analysis of the spectrum, the material exhibits very excellent light absorption performance under ultraviolet light of 200nm-800nm.

[0110] Fig. 9 This is the photoluminescence spectrum of the Cu(I)-MOF crystal luminescent material prepared in Example 1. According to the analysis in the figure, when the wavelength of the excitation light source is 235nm, the light intensity emitted by the material at a wavelength of 555nm is the highest.

[0111] Fig.10This is a diagram of the quantum yield of the Cu(I)-MOF crystal luminescent material prepared in Example 1. According to the diagram, the quantum yield of the light intensity emitted by the material at 325nm under a 310nm excitation light source is close to 100%.

[0112] Example 4

[0113] Example 4 provides a method for preparing a Cu(I)-MOF@PMMA scintillator film material for X-ray scanning imaging, and the preparation method is as follows:

[0114] S1, dispersing 1.5 g of the two-dimensional Cu-MOF crystal luminescent material prepared in Example 1 and 20 g of PMMA raw material in a toluene solution, and then dissolving PMMA in the toluene solvent to obtain a uniformly mixed precursor turbid solution.

[0115] S2, drop the precursor turbid liquid onto the glass substrate and start rapid spin coating until the precursor film is formed.

[0116] S3, placing the precursor film in a constant temperature oven at 50°C for a first annealing for 10 minutes, and then peeling the annealed solidified film from the glass substrate. Then, placing the peeled film in a glass dish, and then placing it in a constant temperature oven at 80°C for a second annealing for 5 minutes, to obtain a two-dimensional Cu-MOF scintillator film material.

[0117] Example 5

[0118] In Example 5, compared with Example 4, the amount of two-dimensional Cu-MOF crystal luminescent material used is 1 g, the amount of PMMA used is 15 g, the first annealing temperature is 40° C., and the second annealing temperature is 70° C.

[0119] Example 6

[0120] In Example 6, compared with Example 4, the amount of two-dimensional Cu-MOF crystal luminescent material used is 2 g, the amount of PMMA used is 10 g, the first annealing temperature is 60° C., and the second annealing temperature is 90° C.

[0121] Fig.11 , 12 13 are actual photographs and X-ray images of the Cu(I)-MOF@PMMA scintillator film material prepared in Examples 4-6 before and after X-ray imaging. It can be seen from the figures that the images imaged by the Cu(I)MOF@PMMA thin film scintillator are very clear and have great potential value in X-ray scanning imaging.

[0122] Fig.14The Cu(I)-MOF@PMMA scintillator film prepared in Example 4 was photographed using a line pair card with standard X-ray resolution. According to the analysis of the figure, the material combined with PMMA to assist in film formation has a high spatial resolution in X-ray scanning imaging, reaching a spatial resolution of 15.5-17.5.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material, characterized in that: The following steps are involved: S1, placing copper nitrate and pyrazole in a reaction kettle, then adding an organic solvent and deionized water, and stirring until dissolved; S2, heating the mixed solution of step S1 to 100°C, reacting for 18-24 hours, cooling, washing with an organic solvent, and drying to obtain a Cu(I)-MOF crystal luminescent material.

2. The method for preparing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 1, characterized in that: The copper nitrate is Cu(NO3)2·2.5H2O, and the molar ratio of copper nitrate:pyrazole is 1.3-2:1.7-2.

5.

3. The method for preparing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 1, characterized in that: During heating in step S2, the temperature is raised to 100°C at a rate of 1-5°C / min.

4. The method for preparing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 1, characterized in that: The organic solvents in steps S1 and S2 are N,N-dimethylformamide and anhydrous ethanol.

5. The method for preparing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 1, characterized in that: In step S1, the stirring time is 5 to 10 minutes, and the stirring rate is 300 to 800 rpm.

6. A pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material as claimed in claim 6 in the preparation of Cu(I)-MOF@PMMA scintillator film material.

8. The use of a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 7 in the preparation of a Cu(I)-MOF@PMMA scintillator film material, characterized in that: The preparation method of the MOF@PMMA scintillator film material comprises the following steps: S1, dispersing a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material and polymethyl methacrylate in a toluene solution to obtain a precursor turbid liquid, then dropping the precursor turbid liquid onto a glass substrate, and spin coating to form a precursor film; S2, placing the precursor film in an oven for a first annealing, then peeling the annealed solidified film from the glass substrate, and performing a second annealing to obtain a MOF@PMMA scintillator film material.

9. The use of a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 7 in the preparation of a Cu(I)-MOF@PMMA scintillator film material, characterized in that: The mass ratio of pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material: polymethyl methacrylate is 1-2:10-20.

10. The use of a pyrazolyl two-dimensional Cu(I)-MOF crystal luminescent material according to claim 7 in the preparation of a Cu(I)-MOF@PMMA scintillator film material, characterized in that: The first annealing temperature is 40-60°C and the time is 10 minutes; the second annealing temperature is 70-90°C and the time is 5 minutes.

Citation Information

Patent Citations

  • Preparation and application of X-ray scintillator based on rare earth oxygen cluster and cuprous iodide cluster

    CN115093436A

  • High spatial resolution x-ray scintillator based on two-dimensional copper iodide (i) halide

    CN116004222A

  • Pyrazolyl-Imidazolium Ligands, Metal Organic Frameworks Comprising the Same and Method of Preparing the Same

    KR1020180008331A